PEMODELAN VOLATILITAS INDEKS HARGA SAHAM DENGAN METODE GARCH DAN E- GARCH : STUDI KASUS PADA JAKARTA STOCK EXCHANGE COMPOSITE INDEX ( JCI ) DAN STRAIT TIMES INDEX (STI ) - Nugraheni, Siwi; Fadilla, Ardhiani; Solihah, Dienni Ruhjatini (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Trading shares of a country has the same or different characteristics as other countries. The characteristics of the market are a reflection of the character of investors who play a role in trading on the stock exchange. Although there are differences or similarities in character on a country's stock exchange, there is something experienced by all stock exchanges in various countries, namely the movement of stock price values and volumes in stock trading dynamically known as volatility. Volatility as a risk that an investor must face in investing requires the ability to predict volatility so that the risk of loss borne by investors can be reduced. The volatility forecasting model with the Garch and E Garch methods is expected to be one of the investors' considerations in making rational investment decisions.